A Brief Assessment of Intelligence Decline in Schizophrenia As Represented by the Difference between Current and Premorbid Intellectual Quotient - Ohi, Kazutaka; Sumiyoshi, Chika; Fujino, Haruo; Yasuda, Yuka; Yamamori, Hidenaga; Fujimoto, Michiko; Sumiyoshi, Tomiki; Hashimoto, Ryota (Frontiers in Psychiatry, 2017)
Patients with schizophrenia elicit several clinical features, such as psychotic symptoms, cognitive impairment and subtle decline of intelligence. The latter two features become evident around the onset of the illness, although they may exist even before the disease onset in a substantial proportion of cases. Here, we review the literature concerning intelligence decline (ID) during the progression of schizophrenia. ID can be estimated by comparing premorbid and current intellectual quotient (IQ) by means of the Adult Reading Test and Wechsler Adult Intelligence Scale (WAIS), respectively. For the purpose of brief assessment, we have recently developed the WAIS-Short Form, which consists of Similarities and Symbol Search and well reflects functional outcomes. According to the degree of ID, patients were classified into three distinct subgroups; Deteriorated, Preserved and Compromised groups. Patients who show deteriorated IQ (Deteriorated group) elicit ID from a premorbid level (≥10-point difference between current and premorbid IQ), while patients who show preserved or compromised IQ do not show such decline (<10-point difference). Furthermore, the latter patients were divided into patients with preserved and compromised IQ based on an estimated premorbid IQ score >90 or below 90, respectively. We have recently shown the distribution of ID in a large cohort of schizophrenia patients. Consistent with previous studies, approximately 30% of schizophrenia patients had a decline of less than 10 points, i.e., normal intellectual performance. In contrast, approximately 70% of patients showed deterioration of IQ. These results indicate that there is a subgroup of schizophrenia patients who have mild or minimal intellectual deficits, following the onset of the disorder. Therefore, a careful assessment of ID is important in identifying appropriate interventions, including medications, cognitive remediation, and social/community services.